Learning Design Based on ELPSA Learning Approach for Elementary School Students - Ummu Khaltsum; Syarifah Aeni Rahman; Andi Mulawakkan Firdaus (Universitas Cokroaminoto Palopo, 2022)
This development research aims to produce Student Worksheet with an ELPSA framework in order to improve students' conceptual understanding skills and to determine the quality of LKS based on aspects of validity, and aspects of practicality. The method used in this research is research and development with a model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research is the development of student worksheets with the ELPSA framework. The instruments used to measure the quality of the developed worksheets are questionnaire sheets for the validity aspect, teacher evaluation sheets for practicality aspects, student response questionnaires, and learning outcomes tests to determine students' conceptual understanding abilities. The quality of the validity of the LKS meets the valid criteria based on the assessment of the validator material experts and media experts, with a percentage of 82.85% included in the very good category. The practical quality of the LKS meets the practical criteria based on the teacher evaluation questionnaire with a percentage of 81.50% which is included in the good category so that the LKS is said to be practical. Student responses to the LKS were obtained from a questionnaire with an average of 44.96 included in the very good category. Meanwhile, to determine student learning outcomes, based on the post-test results of fifth grade students at SD Negeri Sangir, the average score was 91.2 with a mastery percentage of 91.2%, which was included in the highly improved category. Thus, the results of this study indicate that the developed worksheets are said to be suitable for use in the learning process in schools that use KTSP and 2013 curriculum because they meet the quality criteria of student worksheets and can improve students' ability to understand mathematical concepts.